1993
DOI: 10.1016/0736-5748(93)90081-n
|View full text |Cite
|
Sign up to set email alerts
|

Microglia‐derived plasminogen enhances neurite outgrowth from explant cultures of rat brain

Abstract: Recently, we reported the production and secretion of plasminogen (Pg) in cultured rat brain microglia [Nakajima et al., (1992) Fedn. Eur. Biochem. Socs Lett. 308, 179-182]. To investigate the physiological significance of Pg, we determined the effect of Pg on neurite outgrowth of cultured neocortical explants of an embryonic rat brain in serum-free chemically defined medium. Pg markedly enhanced the neurite outgrowth. Although plasmin, which is derived from Pg by activation by urokinase (UK), had a similar ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…1, bottom). Some of the first lines of evidence for this were in vitro studies in which microglia-conditioned media was added to neuronal cultures, resulting in enhanced progenitor cell proliferation and enhanced neuron survival and/or maturation (Nagata et al 1993;Chamak et al 1994;Morgan et al 2004). However, other recent work has shown that culturing NPCs isolated from cortices that lack microglia (PU.1 2/2 ) had no effect on neuron survival or neurogenesis but rather resulted in decreases in neural progenitor cell proliferation and astrogenesis, effects that were rescued by adding wild-type (WT) microglia back to the cultures (Antony et al 2011).…”
Section: Regulation Of Cell Survival Proliferation and Differentiationmentioning
confidence: 99%
“…1, bottom). Some of the first lines of evidence for this were in vitro studies in which microglia-conditioned media was added to neuronal cultures, resulting in enhanced progenitor cell proliferation and enhanced neuron survival and/or maturation (Nagata et al 1993;Chamak et al 1994;Morgan et al 2004). However, other recent work has shown that culturing NPCs isolated from cortices that lack microglia (PU.1 2/2 ) had no effect on neuron survival or neurogenesis but rather resulted in decreases in neural progenitor cell proliferation and astrogenesis, effects that were rescued by adding wild-type (WT) microglia back to the cultures (Antony et al 2011).…”
Section: Regulation Of Cell Survival Proliferation and Differentiationmentioning
confidence: 99%
“…microglia-derived plasminogen may play a role in the regulation of neurite extension through bind ing to the surface of neocortical neurons [58]. Plasmino gen secreted from microglia could also be relevant for extracellular proteolysis, cell migration and synaptogenesis during CNS development [58], Cultured astrocytes and microglia produce and release prostaglandin E2 (PGE2) in response to stimulants such as LPS, tissue plasminogen activator (TPA), and lymphokines [59]. Since the sensitivity to these stimuli dif fers between astrocytes and microglia, PGE2 may differ entially regulate astrocyte proliferation under different physiological conditions, acting in an autocrine fashion for astrocytes and in a paracrine fashion for microglia [59].…”
Section: Modulation O F Microglial Activity By Noncytokinementioning
confidence: 99%
“…In the developing brain, diffuse noradrenergic affcrences are present in those areas where the transient accumula tion of macrophages occurs [56,57], Another aspect of neuron-glia interrelationships is that the interaction between neurons and glia/microglia may be bidirec tional, e.g. microglia-derived plasminogen may play a role in the regulation of neurite extension through bind ing to the surface of neocortical neurons [58]. Plasmino gen secreted from microglia could also be relevant for extracellular proteolysis, cell migration and synaptogenesis during CNS development [58], Cultured astrocytes and microglia produce and release prostaglandin E2 (PGE2) in response to stimulants such as LPS, tissue plasminogen activator (TPA), and lymphokines [59].…”
Section: Modulation O F Microglial Activity By Noncytokinementioning
confidence: 99%
“…Apod (47), Dcn (48), Dspg3 (49), Mdm2 (50), Plg (51), Sgk2 (52), and Tnfrsf18 (53)) and/or neuronal development (e.g. Apod (54), Dcn (54,55), Dspg3 (49,56), Plg (57), and Plxnb3 (58)). To identify pathways and/or biological processes impacted by Complex treatment, we used the Ingenuity Pathways Knowledge Base to assess relationships between these differentially expressed genes.…”
Section: Discussionmentioning
confidence: 99%